Transcriptome Analysis Reveals the Role of Cellular Calcium Disorder in Varicella Zoster Virus-Induced Post-Herpetic Neuralgia - Wu, Songbin; Yang, Shaomin; Ou, Mingxi; Chen, Jiamin; Huang, Jiabing; Xiong, Donglin; Sun, Wuping; Xiao, Lizu (Frontiers in Molecular Neuroscience, 2021)
As a typical neuropathic pain, post-herpetic neuralgia (PHN) is a common complication of herpes zoster (HZ), which seriously affects the normal life and work of patients. The unclear pathogenesis and lack of effective drugs make the clinical efficacy of PHN unsatisfactory. Here, we obtained the transcriptome profile of neuroblastoma cells (SH-SY5Y) and DRG in rats infected with varicella zoster virus (VZV) by transcriptome sequencing (RNA-Seq) combined publicly available gene array data sets. Next, the data processing of the transcriptome map was analyzed using bioinformatics methods, including the screening of differentially expressed genes (DEGs), gene ontology (GO) and the Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis. Finally, real-time fluorescent quantitative PCR (qRT-PCR) was used to detect the expression of calcium-related genes, calcium fluorescent probes and calcium colorimetry were used to evaluate the distribution and content of calcium ions in cells after VZV infection. Transcriptome data analysis (GO and KEGG enrichment analysis) showed that calcium disorder played an important role in SH-SY5Y cells infected by VZV and dorsal root ganglion (DRG) of the PHN rat model. The results of qRT-PCR showed that the expression levels of calcium-related genes BHLHA15, CACNA1F, CACNG1, CHRNA9 and STC2 were significantly up-regulated, while the expression levels of CHRNA10, HRC and TNNT3 were significantly down-regulated in SH-SY5Y cells infected with VZV. Our calcium fluorescent probe and calcium colorimetric test results showed that VZV could change the distribution of calcium ions in infected cells and significantly increase the intracellular calcium content. In conclusion, our results revealed that the persistence of calcium disorder caused by VZV in nerve cells might be a crucial cause of herpetic neuralgia, and a potential target for clinical diagnosis and treatment of PHN.